A Study of Folk Dance Learning by University Students - Sarula, Guo (Lavai - International Journal of Education, 2024)
In the folk dance traditions of every country in the world, there is a dance language and artistic expressions that express the characteristics of the nation. Dance is expressed through emotional movement using dance techniques. University dance teaching methods have a great impact on the quality and level of dance education. The article will present the results of an experimental study of a method of supporting students' folk dance learning. A total of 60 students studying dance at the Hulunbuir University of Inner Mongolia Autonomous Region, China, and the School of Dance Arts of the Mongolian State University of Music and Drama of the 1st and 2nd year of the dance teacher's class participated in our experiment. The performance of students in folk dance was evaluated within 5 criteria and the results were calculated, and the performance of students in folk dance improved by 1-2 levels. When the results of the pilot study were analysed using a T-test, the results of the evaluation of students' folk-dance performance showed that the students' knowledge of dance (p = 0.001, t = 28.926), dance elements (p =0.001, t = 24.523), analysis and interpretation (p = 0.05, t = 19.467), understanding of dance (p = 0.001, t = 29.712), and dance composition and improvisation (p = 0.001, t = 19.827) were statistically significant.